2018
DOI: 10.1515/hf-2017-0108
|View full text |Cite
|
Sign up to set email alerts
|

Process optimization of lignin conversion into value added chemicals by thermochemical pretreatment and electrooxidation on a stainless steel anode

Abstract: Wheat straw soda lignin was subjected to thermochemical (TC) pretreatment at low to moderate temperatures followed by electrooxidation (EO) on an SS-304 anode to produce some value-added organic chemicals. The influence of independent process variables on the product yield of major organic chemical groups, namely, aromatic carbonyl compounds (COarom), aromatic hydrocarbons (HCarom), and aliphatic hydrocarbons (HCaliph), was studied. Response surface methodology (RSM) was used to optimize the process conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Results from the technoeconomic and energy assessment were analyzed by the statistical software Design-Expert 8.0.7.1 (Stat-Ease Inc., Minneapolis, MN, USA). The response surface methodology (RSM) was applied, which is a collection of statistical and mathematical techniques needed for developing, improving and optimizing processes (Singh and Ghatak 2017). This methodology was extensively applied at industrial levels, particularly in situations, where several input variables influence the process performance (Myers et al 2016).…”
Section: Statistical Assessment and Optimizationmentioning
confidence: 99%
“…Results from the technoeconomic and energy assessment were analyzed by the statistical software Design-Expert 8.0.7.1 (Stat-Ease Inc., Minneapolis, MN, USA). The response surface methodology (RSM) was applied, which is a collection of statistical and mathematical techniques needed for developing, improving and optimizing processes (Singh and Ghatak 2017). This methodology was extensively applied at industrial levels, particularly in situations, where several input variables influence the process performance (Myers et al 2016).…”
Section: Statistical Assessment and Optimizationmentioning
confidence: 99%
“…11 Among electrochemical approaches, the electro-oxidation of lignin at the anode is the most common one studied. 12 Even if electrocatalytic approaches similar to that adopted in the present study were reported in the literature for other combinations of lignins and working electrodes, [13][14][15] investigations regarding the electrochemical conversion of P1000 lignin, up to now, are absent. Only a few studies are available concerning its chemical valorisation through inorganic catalysts, such as CuMgAlO x or NiMo sulphide, in organic solvents under harsh reaction conditions.…”
Section: Introductionmentioning
confidence: 90%
“…Syringaldehyde and acetovanillone were formeda th igher current densities of 6.71 mA cm À2 and 4.47 mA cm À2 respectively. [121] 7.2. Integrated electrocatalysis:I onic-liquid and deep-eutectic-solvent electrolytes Ionic liquids are popular substitutes for aqueous electrolytes in biomass electrocatalysis due to their enhanced conductivity, non-volatility,g reater solubilizing capacity for lignin, thermal and chemical stability, and aw ider electrochemical window compared to water.…”
Section: Stainless Steelmentioning
confidence: 99%
“…Optimized current density (2.24 mA cm −2 ) and reaction time (12 h) favored the formation of 24.7 % aromatic carbonyl compounds (e.g., 6.7 % vanillin and 11.4 % acetosyringone), while a different optimized current density (2.24–2.28 mA cm −2 ) with a shorter reaction time (0–0.85 h) was optimal for the formation of 16.1 % aromatic hydrocarbons (12 % o ‐xylene and 3 % toluene). Syringaldehyde and acetovanillone were formed at higher current densities of 6.71 mA cm −2 and 4.47 mA cm −2 respectively …”
Section: Electrocatalytic Treatment Of Ligninmentioning
confidence: 99%